PENGEMBANGAN DESAIN KEMASAN PRODUK UNTUK MENINGKATKAN DAYA SAING PENJUALAN PRODUK PADA TOKO OLEH-OLEH JOGLO - Atika Jauharia Hatta Hatta; Cahyo Indraswono; Daniel Joel Immanuel Kairupan; Bianka Andriyani (Jurnal Ekonomi Dan Bisnis, 2026)
This activity aims to increase the sales of Joglo Souvenir Shop's product through the development of product packaging design innovations. This SME is a typical Central Javanese souvenirs business located in Pedan District, Klaten Regency, Central Java, which sells spinach chips, bitter melon chips, kenikir, intestines, mushrooms, and wedang uwuh. The majority activity of this SME just change the packaging form, while for wedang uwuh and empon-empon, the SME produces itself in the form of sachet drinks such as tea bags. The main problem of this SME is relying on buyers who visit the Pedan area, while the product packaging is still less attractive to buyers due to the lack of packaging design references, resulting in less interest in buying goods. The solution to overcome this problem is to provide training and mentoring for SMEs to create innovative packaging designs to increase buyer interest. The method used in this activity is a participatory training and supervision method, partners will always be involved in every stage of the activity. The targeted result is that SME are able to create attractive packaging designs, and resulting five packaging forms that can be used as references for having advantages compared to their competing products.